Indian National Congress in Jammu and Kashmir. - Nabi, Shabnam (IJRDO - Journal of Social Science and Humanities Research, 2016)
The Jammu & Kashmir state very well known around the world as the crown of India because of its beauty and is situated at the top of India. The borders of this state here touch the boundaries of China and Pakistan. The people of this state were oppressed for centuries together by different rulers from time to time. Being a princely state in British rule merged with union ofIndia after independence. The government of the state is run by India and is financially and fiscally integrated into the union of India. The Congress party played an important part in making the state of J&K as an intrinsic part of India and its body politics. The underlying objective of the initiative was to understand the effective governance of Indian National Congress and the state led ruling parties in Jammu & Kashmir from time to time.